2013
DOI: 10.1590/s0101-32622013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades matemáticas iniciais em crianças surdas e ouvintes

Abstract: RESUMO:O presente estudo tem como objetivo investigar o conhecimento de procedimentos e conceitos matemáticos em crianças surdas da educação infantil. Até o momento, existe uma grande escassez de estudos sobre o desenvolvimento de conceitos e procedimentos matemáticos em crianças surdas de idade pré-escolar. Os poucos trabalhos existentes sugerem que as crianças surdas têm difi culdades em aprender a sequência numérica. Contudo, não há qualquer evidência conclusiva a respeito das causas desta difi culdade. Os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Some studies showed significant differences between deaf and hearing individuals in response times for numerical magnitude comparison (Epstein et al, 1995;Marschark et al, 2003). However, other researchers found no significant differences between deaf and hearing individuals in their number representation processes (Zarfaty et al, 2004;Arfé et al, 2011;Barbosa, 2013). Whether numerical magnitude processing (symbolic, non-symbolic) is a predictor of the arithmetical ability of the deaf population or not still needs to be verified.…”
Section: Numerical Magnitude Processing and Mathematical Abilitymentioning
confidence: 87%
See 2 more Smart Citations
“…Some studies showed significant differences between deaf and hearing individuals in response times for numerical magnitude comparison (Epstein et al, 1995;Marschark et al, 2003). However, other researchers found no significant differences between deaf and hearing individuals in their number representation processes (Zarfaty et al, 2004;Arfé et al, 2011;Barbosa, 2013). Whether numerical magnitude processing (symbolic, non-symbolic) is a predictor of the arithmetical ability of the deaf population or not still needs to be verified.…”
Section: Numerical Magnitude Processing and Mathematical Abilitymentioning
confidence: 87%
“…Zarfaty et al (2004) compared 3-and 4-year-old deaf and hearing children's performance in number representation tasks and found out the better performance of deaf children in the spatial task and no difference from hearing counterparts in the temporal tasks. Barbosa (2013) conducted a similar study with Brazilian deaf children aged 5-6 years, and found out the young deaf children's number representation ability was as good as that of hearing children, which supported the previous research findings by Zarfaty et al (2004). Arfé et al (2011) investigated number representation ability of deaf primary school children with cochlear implants in a digit comparison task and an analogic comparison task, and also found out the better performance of deaf children in the analogic task and no difference from hearing children in the digit comparison task.…”
Section: Numerical Magnitude Processing In Hearing-impaired and Deaf mentioning
confidence: 99%
See 1 more Smart Citation
“…, observamos nos últimos anos um quantitativo significativo de investigações acadêmicas com enfoque nessa área. Entre elas, destacamos inicialmente: Aroldo Jr, Ramos e Thoma (2013); Barbosa (2013;2014), Fernandes e Healy (2013; 2016). As reflexões apresentadas em cada estudo representam a importância em perceber o ambiente escolar como um lugar privilegiado de diferentes visões, aprendizagens e singularidades discentes.…”
Section: No Contexto Da Educação Matemática Inclusiva -Emi[i]unclassified
“…De modo geral, a investigação da cognição numérica na criança surda usuária de Libras tem se concentrado em examinar a influência da linguagem no desenvolvimento do conhecimento matemático. O tempo de exposição à Língua (Barbosa, 2013), bem como a idade em que ocorreu o contato inicial com a Língua de Sinais (Madalena, Marins & Santos, 2012), por exemplo, foram apontados como fatores que interferem no desempenho dos alunos, identificando-se forte relação entre desenvolvimento linguístico e formação de conceitos numéricos.…”
Section: Introductionunclassified